Vox Unpunished Frankness: distorted memory(ies) in the Spanish new right (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Within the framework of the rise of the "new rights" in different Western democratic systems, this article analyzes the position of VOX against the struggle of memorial organizations and memory policies in Spain. We will do this by analysing the public message of its leadership, as well as interviews held with affiliates and party supporters. We will set out a political discourse analysis, in the broader theoretical framework of the lacanian left.Our main hypotheses is that Vox rejection to these historical memory policies is possible on the background of a structural transformation in the way social bonds are constituted, the pseudo Capitalist Discourse (Lacan). We would like to underline here one of the many implications of this change: the denial of any genealogical operation, and therefore, of any politics of memory, which would make evident the contingency of the full-fledged image by which the neoliberal subjectivity submits itself to the superegoic command to unlimited enjoyment.
Keywords: Vox, Politics of memory, Political subjectivity, Capitalist Discourse